Partisipasi Masyarakat dalam Penyelenggaraan Program Kursus Komputer Bebas Biaya - Azminatul Muna; Muarifuddin Muarifuddin (Departement of Mathematics Education, 2023)
This study aims to describe the marketing strategy of the Mizz@comp course and training institute in attracting community participation, the forms of community participation and the factors that influence community participation in organizing free computer course programs. The research design in this research is descriptive qualitative. The results obtained in this study were that LKP Mizz@comp carried out four marketing strategies, namely market segmentation, market targeting, positioning and marketing mix. The forms of community participation in organizing computer courses are that the community does not actively participate in planning, but the community actively participates in implementing and utilizing the results. Factors that influence community participation are internal factors, the desire of course participants, age, gender, level of education, and income level. While the external factors are the intensity of socialization, support from the government and the activeness of the facilitators.